2014
DOI: 10.2215/cjn.10391012
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Tubule Function and Response to Acidosis

Abstract: SummaryThe human kidneys produce approximately 160-170 L of ultrafiltrate per day. The proximal tubule contributes to fluid, electrolyte, and nutrient homeostasis by reabsorbing approximately 60%-70% of the water and NaCl, a greater proportion of the NaHCO 3 , and nearly all of the nutrients in the ultrafiltrate. The proximal tubule is also the site of active solute secretion, hormone production, and many of the metabolic functions of the kidney. This review discusses the transport of NaCl, NaHCO 3 , glucose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
208
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(216 citation statements)
references
References 97 publications
4
208
0
4
Order By: Relevance
“…Changes in ammoniagenesis, such as during metabolic acidosis, are associated with changes in the expression of SNAT3, but not expression of apical Na 1 -dependent neutral amino acid transporter-1 (50). Ammoniagenesis primarily involves phosphate-dependent glutaminase, glutamate dehydrogenase, a-ketoglutarate dehydrogenase, and phosphoenolpyruvate carboxykinase (PEPCK) (47,51), and complete glutamine metabolism generates two NH 4 1 and two HCO 3 2 ions per glutamine. The bicarbonate produced is then transported across the basolateral membrane via electrogenic sodium-coupled bicarbonate co-transporter, isoform 1A (NBCe-1A), and serves as "new bicarbonate" generated by the kidney.…”
Section: Renal Ammonia Handlingmentioning
confidence: 99%
“…Changes in ammoniagenesis, such as during metabolic acidosis, are associated with changes in the expression of SNAT3, but not expression of apical Na 1 -dependent neutral amino acid transporter-1 (50). Ammoniagenesis primarily involves phosphate-dependent glutaminase, glutamate dehydrogenase, a-ketoglutarate dehydrogenase, and phosphoenolpyruvate carboxykinase (PEPCK) (47,51), and complete glutamine metabolism generates two NH 4 1 and two HCO 3 2 ions per glutamine. The bicarbonate produced is then transported across the basolateral membrane via electrogenic sodium-coupled bicarbonate co-transporter, isoform 1A (NBCe-1A), and serves as "new bicarbonate" generated by the kidney.…”
Section: Renal Ammonia Handlingmentioning
confidence: 99%
“…Because this has been recently reviewed in this series (18), only a few comments will be made. The signals for these changes are often thought to be pH per se, either intracellular or extracellular.…”
Section: Regulation Of Hco 3 2 Reabsorption In the Proximal Tubulementioning
confidence: 99%
“…have also been shown to alter NH 3 production. The enzymatic and transporter changes that facilitate enhanced ammoniagenesis during acidosis have recently been reviewed in this series (18). The transport of the produced NH 4 1 along the nephron and into the urine is a complex process that is still a topic of intense study (Figure 6).…”
Section: Nhmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37) The proximal tubule contributes to fluid, electrolyte, and nutrient homeostasis by reabsorbing 60-70% of the water and NaCl, 70-80% of the phosphate, and nearly all of the nutrients (i.e., glucose, amino acids) in the ultrafiltrate. 66,67) In the proximal tubules, ezrin is concentrated at cell surface structures such as microvilli in the wild-type kidney. 68) In our study, the Vil2 KD/KD mouse kidney showed no obvious histological differences from the wild-type mouse kidney.…”
Section: Kidneymentioning
confidence: 99%